“Tap, tap, flap, flap.” Ludic Seriality, Digitality, and the Finger - Heilmann, Till A. (Eludamos: Journal for Computer Game Culture, 2014)
This article tries to answer the question, “What is ‘digital’ about digital media?” Building on the concept of ludic seriality as proposed by Shane Denson and Andreas Jahn-Sudmann and taking as an example the popular mobile Game Flappy Bird, it discusses the serial character of gameplay, in particular the intra-ludic serialization of in-game and operator actions. The article argues that the principle of digitality relates to the fingers of the human hand and the corresponding cultural techniques, from the ancient art of finger-counting which brought forth the abstract number concept to our current every day use of buttons and keys to operate digital devices.